2020
DOI: 10.1007/s11664-020-08188-6
|View full text |Cite
|
Sign up to set email alerts
|

Alloy Stability of Ge1−xSnx with Sn Concentrations up to 17% Utilizing Low-Temperature Molecular Beam Epitaxy

Abstract: The binary alloy germanium tin has already been presented as a direct group IV semiconductor at high tin concentrations and specific strain. Therefore, it offers a promising approach for the monolithic integrated light source towards the optical on-chip communication on silicon. However, the main challenge faced by many researchers is the achievement of high tin concentrations and good crystal quality. The key issues are the lattice mismatch to silicon and germanium, as well as the limited solid solubility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Therefore, there is a need to use non-equilibrium fabrication processes to incorporate larger amounts of Sn into Ge and avoid its segregation. Promising methods to fabricate Ge 1−x Sn x alloys are molecular-beam epitaxy (MBE) [9][10][11], chemical vapour deposition (CVD) [12,13], and ion implantation followed by non-equilibrium annealing like ns-range pulsed laser melting (PLM) [14] or the ms-range flash-lamp annealing [15]. Wirths et al demonstrated the first group-IV laser using a Ge 1−x Sn x alloy grown on Ge substrates by CVD [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to use non-equilibrium fabrication processes to incorporate larger amounts of Sn into Ge and avoid its segregation. Promising methods to fabricate Ge 1−x Sn x alloys are molecular-beam epitaxy (MBE) [9][10][11], chemical vapour deposition (CVD) [12,13], and ion implantation followed by non-equilibrium annealing like ns-range pulsed laser melting (PLM) [14] or the ms-range flash-lamp annealing [15]. Wirths et al demonstrated the first group-IV laser using a Ge 1−x Sn x alloy grown on Ge substrates by CVD [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, epitaxial growth of GeSn crystals is very challenging because of the huge lattice mismatch between Ge and α-Sn (14.7%), the surface segregation of Sn in Ge [9] and the extremely low equilibrium solubility of Sn in Ge (∼ 1%). [10] Recently, many research groups have successfully fabricated high-quality GeSn epitaxial films [11][12][13] and GeSn photodetectors, [14,15] but photovoltaic research on GeSn is still in its initial stage. Conley et al [8,16] have manufactured highquality GeSn films on Si using a relaxed Ge buffer layer, which can be used in high-efficiency multi-junction PV and TPV cells.…”
Section: Introductionmentioning
confidence: 99%
“…Future development of hyperdoped Ge:Au should also investigate how its properties compare to those of state-ofthe art Ge-Sn alloys. Critical properties to compare should include sub-band-gap absorption (absorption coefficient and wavelength-dependent edge) and properties that currently limit Ge-Sn devices (thermal metastabilty [61,62] and relatively high leakage current [43,44]) compared with commerical III-V and II-VI semiconductor devices.…”
Section: Future Workmentioning
confidence: 99%